Paraquat poisoning-a dreadful and lethal poisoning: a case report of two cases from East Godavari, Andhra Pradesh, India - Venkatanand, K.; Agrawal, Aakash; Sarma, M. B. R. (International Journal of Research in Medical Sciences, 2017)
Paraquat, a bipyridyl compound is used as a contact herbicide. It is a highly lethal compound with high mortality rates in cases of intentional ingestion for suicidal purpose. Although widely used in East Godavari District of Andhra Pradesh, India, cases of poisoning with this herbicide have been rarely reported from this region. This compound affects the lungs (leading to pulmonary fibrosis) and the kidney (leading to Acute Kidney Injury) the most. Ingestion of small quantities can cause death and lack of a specific antidote and specific treatment guidelines makes it a dreadful and lethal poison. We report two cases of suicidal ingestion of Paraquat which presented to the emergency department of KIMS and RF hospital, Amalapuram, East Godavari District, Andhra Pradesh, India.